97-LB: Bringing Simulation Technologies to People with T1D: A Pilot Study - COLMEGNA, PATRICIO; BISIO, ALESSANDRO; MCFADDEN, RYAN; WAKEMAN, CHRISTIAN A.; OLIVERI, MARY C.; NASS, RALF; BRETON, MARC D. (Diabetes (New York, N.Y.), 2021)
Background: Researchers have extensively used metabolic simulators as a fast, inexpensive, and safe way of testing novel treatment strategies. This work aims to bring this technology to people with T1D to enable unique patient/data interactions. Methods: A 5-week pilot study was carried out in 15 adults with T1D using Control-IQ technology (age 36±13 years, HbA1c 6.5±0.7%) to evaluate acceptance of the proposed Web-Based Simulation Tool (WST). The study consisted of 1 week of observation (Phase 1) and 4 weeks of interaction with WST (Phase 2). Data were automatically collected via Tandem Diabetes Care t:connect web application, and used to generate personalized models of the participants’ glucose metabolism. Results: Success rate in generating models was 86.4%, achieving an average MARD of 7.4±3.2%. Interaction time was 15.8±10.7 min per week. Comparing Phases 1 and 2, no variation was detected in time in range 70-180 mg/dl (80.1 [70.4,89.6]% vs. 80 [69.7,87.9]%). Time in 70-250 mg/dl increased slightly (94.2 [90.3,95.7]% vs. 96.2 [92.1,97.9]%), especially overnight (92.8 [88.3,98.2]% vs. 97.2 [91.8,99.6]%), and for participants who modified their pump settings based on WST simulations (90 [88.7,92.4]% vs. 94.5 [87.1,99.6]%). One subject tested COVID positive during the study and was excluded from this analysis due to abnormal hyperglycemia. Analysis of Diabetes Distress Scale (DDS)-17 pre and post-system use shows a reduction in diabetes-related distress (2.2 [1.7,3.4] vs. 2 [1.7,2.4]). Trust, ease of use, and usefulness scores were 80 [60,80]%, 60 [60,80]%, and 80 [60,80]%, respectively. During the follow up interviews, 10 participants reported they enjoyed using WST and would implement it into their diabetes management; 2 did not like the system but see the potential of it for other people; 3 participants did not like the system at all. Conclusions: Evidence from this study suggests that simulation technologies may empower people with T1D, making them more confident in their diabetes self-management.